Vilnius: war losses in the years 1944–1945 - Stravinskienė, Vitalija (City and War, 2021)
The article, based on collections of documents, archival materials and historiography, discusses the material losses caused to the city of Vilnius by the war battles in 1944 and railway explosion in 1945. The author focuses on the scope of material damage, the mechanism of their detection and the initial stage of setting the physical losses. The centre part of the city suffered the most during the combats, but the explosion of the train ammunition at the beginning of 1945 increased the material losses even further. The special commission to determine the physical losses estimated that the damage to the city’s economy and culture amounted to 1 billion 129 million rubles.